PENYULUHAN PEMANFAATAN SUMBER AIR TERBATAS DI DAERAH PERBUKITAN TIBU LILIN KECAMATAN LEMBAR KABUPATEN LOMBOK BARAT - Negara, I Dewa Gede Jaya; Saidah, Humairo; Rohani, Rohani; Suparjo, Suparjo; Pracoyo, Atas; Supriyadi, Anid; Suroso, Agus (Universitas Mataram, 2024)
The people of Tibu Lilin Hamlet are a hamlet located in the hills south of Gumise Hamlet and located just to the north of Selamat Harbor. Along the village road are steep hillsides that have been used as villages, so the topography of this hamlet is very irregular. The community's water source during the rainy season comes from springs around the village in the form of water from springs, well water and seepage water from rock fragments on existing hillside cliffs. Meanwhile, during the dry season, most of the water sources dry up and only one or two locations have water with very minimal potential. Water shortages during the dry season are met by buying water from collectors who transport it by truck or tanker to Tibu Lilin Hamlet. Therefore, this service aims to educate the community about how to utilize limited water sources around the hills to help provide community water. The service was carried out in the stages of location coordination, location survey, outreach activities, discussion and question and answer as well as evaluation. Counseling was provided in the form of water storage methods, water storage tank methods and ways of managing water sources in mutual cooperation. This service has succeeded in providing the Tibu Lilin community with knowledge about water sources, how to collect water and manage water sources together. The community has been shown how to make water reservoirs and how to make pipe networks to channel water to the hamlet.